Early Titration of Oxygen During Mechanical Ventilation Reduces Hyperoxemia in a Pilot, Feasibility, Randomized Control Trial for Automated Titration of Oxygen Levels. (9th June 2022) - Pannu, Sonal R.; Exline, Matthew; Klamer, Brett; Brock, Guy; Crouser, Elliott D.; Christman, John W.; Diaz, Philip
Abstract : OBJECTIVES: Timely regulation of oxygen (Fio 2 ) is essential to prevent hyperoxemia or episodic hypoxemia. Exposure to excessive Fio 2 is often noted early after onset of mechanical ventilation. In this pilot study, we examined the feasibility, safety, and efficacy of a clinical trial to prioritize Fio 2 titration with electronic alerts to respiratory therapists. STUDY DESIGN: Open-labeled, randomized control pilot trial. SETTING: Medical ICU. SUBJECTS: Adults requiring mechanical ventilation. INTERVENTIONS: Protocolized oxygen titration was initiated one hour after initiation of mechanical ventilation. When Spo2 exceeded 92% while on Fio2 ≥ 0.5, an electronic alert to respiratory therapists was triggered at 30-minute intervals. In the control arm, respiratory therapists titrated Fio 2 by standard physician's orders. MEASUREMENTS AND MAIN RESULTS: The primary end point was to determine if early Fio 2 titration based on automated alerts was feasible in terms of reducing hyperoxemia. Secondary analyses included the number and frequency of alerts, mechanical ventilation duration, and ICU length of stay. Among 135 randomized patients, 72 were assigned to the intervention arm and 63 to the control arm. A total 877 alerts were sent. Exposure to hyperoxemia was significantly reduced in the intervention group by a median of 7.5 hours (13.7 [interquartile range (IQR), 2.9–31.1] vs 21.2 [IQR, 10.9–64.4]; p < 0.0004). Maximal Fio 2 titration during the first quartile resulted in significant reduction in mechanical ventilation duration and ICU stay. Minor hypoxemic events (Spo 2 < 88%) represented 12% of alerts, 9% were transient and responded to a single Fio 2 increase, whereas 3% of alerts were associated with recurrent transient hypoxemia. CONCLUSIONS: Our pilot study indicates that early Fio 2 titration driven by automated alerts is feasible in the ICU, as reflected by a statistically significant reduction of hyperoxemia exposure, limited consequential hypoxemia, and reduced ICU resource utilization. The encouraging results of this pilot study need to be validated in a larger ICU cohort.